Genetic investigation of a Tunisian family with Lynch syndrome: a case report - Abdelmaksoud-Dammak, Rania; Ammous-Boukhris, Nihel; Guidara, Souhir; Charfi, Slim; Feki, Ameni; Guirat, Manel; Daoud, Rahma; Kamoun, Hassen; Sellami-Boudawara, Tahya; Khanfir, Afef; Mokdad-Gargouri, Raja (Frontiers in Oncology, 2026)
PurposeThis study aimed to characterize the clinical and molecular features of a Tunisian family suspected of Lynch syndrome (LS) and identify the segregating pathogenic variant(s).MethodsA three-generation consanguineous family from the south of Tunisia with six members was recruited. Clinical diagnosis of LS was suspected according to the criteria of Amsterdam. A comprehensive molecular analysis was conducted, including immunohistochemical staining for mismatch repair (MMR) proteins, microsatellite instability (MSI) testing, targeted next-generation sequencing (NGS), and confirmatory Sanger sequencing. Iterative Threading ASSEmbly Refinement (I-TASSER) was used to analyze changes in the functional domains of mutant proteins.ResultsFive members of the family developed cancer before the age of 45, including four cases of colorectal cancer and one case of glioblastoma. Immunohistochemical analysis of the proband showed complete loss of MSH2 and MSH6 protein expression, consistent with a high MSI (MSI-H) phenotype. Germline testing identified a pathogenic frameshift variant in MSH2 (NM_000251: c.687delA, p.Ala230LeuTer16) in the proband, her father, and two of her brothers, whereas her healthy sister did not carry the variant. An additional germline pathogenic variant in MUTYH (NM_001048171: c.1143_1144dupG, p.Glu382GlyTer43) was detected only in the proband’s father and one of her brothers and was absent in the proband. Moreover, the proband later developed an extracolonic malignancy, a right ovarian tumor. NGS analysis of the tumor tissue revealed a pathogenic BRCA2 variant (c.1813delA, p.Ile605TyrTer9), which provides a potential target for personalized therapy. This case report highlights the co-segregation of a rare pathogenic MSH2 variant in a Tunisian family and underscores its clinical implications for improving the management and surveillance of patients with Lynch syndrome.